(untitled) (Research, Society and Development, 2019)
This work is the result of research on the implementation process of the Program of Support to the Federal Universities Restructuring and Expansion Plan (REUNI), for the creation of Bachelor of Science and Technology courses, and Engineering courses at the Federal University of Vales do Jequitinhonha. and Mucuri (UFVJM), on the campus of Diamantina and Teófilo Otoni. To achieve the results, a documentary and bibliographic research was carried out, in which to analyze minutes, notices, pedagogical projects and information available in the Integrated Academic Management System, comparing them with the objectives proposed by the Ministry of Education for the implementation of the REUNI Program. at UFVJM. The research showed that the set of indicators agreed with the Ministry of Education was not entirely achieved with the implementation of REUNI in UFVJM, despite the commitment of deans and deans, directors, coordinators and teachers of the institution, pointing out problems with infrastructure feasibility. suitable for teaching practice, difficulty in contracting teachers and administrative and academic barriers that can hinder the consolidation of courses with quality standards, worthy of the renowned Brazilian public universities.